2017
DOI: 10.3390/app7030222
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chromium (VI) on Calcium Phosphate: Mechanisms and Stability Constants of Surface Complexes

Abstract: Abstract:The adsorption of chromate on octacalcium phosphate (OCP) was investigated as a function of contact time, surface coverage, and solution pH. The ion exchange method was adapted to establish the interaction mechanism. Stoichiometry exchange of H + /OH − was evaluated at a pH range of 3-10, and obtained values ranged between 0.0 and 1.0. The surface complexes formed between chromate and OCP were found to be > S(HCrO 4 ) and > S(CrO 4 ). The logarithmic stability constant logK 1-1 , and the logK 10 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The Freundlich model is an empirical expression describing adsorption onto heterogeneous surfaces, having the adsorbent surface sites with a variation of binding energies. In this case, the equation also in its linear form is ln [ Cr ] c,e = ln k f + 1 __ n ln [ Cr ] c,e (8) where k f and n are parameters related to the Freundlich model.…”
Section: Modeling Of Adsorption Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Freundlich model is an empirical expression describing adsorption onto heterogeneous surfaces, having the adsorbent surface sites with a variation of binding energies. In this case, the equation also in its linear form is ln [ Cr ] c,e = ln k f + 1 __ n ln [ Cr ] c,e (8) where k f and n are parameters related to the Freundlich model.…”
Section: Modeling Of Adsorption Isothermsmentioning
confidence: 99%
“…The data of the amount of chromium(VI) adsorbed on the MWCNTs (mg/g) and the metal concentration remaining in solution (mg/L) are fitted to the Langmuir and Freundlich models represented by Eqs. (7) and (8), respectively. The relative parameters obtained from the fit are listed in Table 5.…”
Section: Effect Of Carbon Nanotubes Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…Included in this special issue is another article on heavy metal remediation from industrial wastewater by Elyahyaoui et al [22]. Phosphate materials, particularly calcium phosphate, have been studied as effective adsorbents for heavy metals from wastewaters and polluted soils.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…However, there is a lack of understanding of the mechanisms of heavy metal immobilization that involves protonation/deprotonation of surface hydroxyl groups and their interaction with the metal oxyanion. Therefore the article entitled "Adsorption of Chromium (VI) on Calcium Phosphate: Mechanisms and Stability Constants of Surface Complexes" [22] investigated the mechanisms of complexation of hexavalent chromium with low-crystallized octacalcium phosphate. The obtained results suggested that Cr (VI) adsorption on octacalcium phosphate was of an electrostatic nature in acidic solutions, and of a chemical nature in lower acidic to alkaline solutions.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%